On the role of designing ablution tub based on ergonomics perspective / Diana Mohamed Raif - Mohamed Raif, Diana (2013)
Consequently, lot of discussion and the approach adopted during the practice of ablution unlawful. Ironically, most of the facilities in the mosque were designed without accommodating the Muslims need in performing ablution, especially the importance of hygienically, conveniently and efficiently when perform the wudhu’. This research focuses on the design of the wudhu’ facility to accommodate the Muslim needs in performing ablution by considering the design that it can be adapted to the compact, simple and budget. It is also environment-friendly design and safety sanitary standard. The methodology that will be used in this study is ergonomic approach with the involvement of competence users. It is aimed at obtaining a design based on user’s expectations as well as safety and comfort. Finally, the study found that the practice of ablution has sparked a variety of architectural ablution place since time immemorial. Therefore, this research will cover the design of a place to take ablution and suitability of use in terms of Islamic law. A conceptual study on the ergonomic of a product development moreover will discuss about the wudhu’ facility to accommodate the Muslim needs in performing ablution.